Complex systems approach and critical thinking in the construction of the research project about the youth in a “marginalized” community in Merida, Yucatan, Mexico - Sidorova, Ksenia; Quiroz Carranza, Roxana; Rivero Pérez, Astrid Karina (Journal of Sociocybernetics, 2014)
The paper discusses the construction of a collective research project focused on the analysis of the youth from a “marginalized” urban area. The subjects of the research are all students of a high school, created by a local university specifically for the needs of their community. We look into the processes of their construction as knowing subjects that possess their own ideas on what it means to be young, participate in personal networks, and have had a unique experience related to the human rights, which more than often are violated in the case of “marginalized” youth. In the paper we discuss the very elaboration of the research object. Based on the constructivist paradigm of the systems approach of Rolando Garcia, our research has led us to make explicit our own standing on the empirical problem we have chosen and thus the epistemological and theoretical position we adopt to construct the research problem. The “parts” and the “processes” our system is made of are the product of our standing on the issue we analyse in the research. Adherents to the “epistemology of the south” of Boaventura De Sousa Santos and the critical perspective on culture and development of Esteban Krotz, we apply “alternative” concepts to “name” the empirical referents and serve of the complex systems thinking to reveal the “other” side of the urban area known as the “south” of Mérida. Marginalized, poor and violent, according to the official and media discourse, in our research it also stands out as a context of social injustice, racism, and discrimination in which some young people have risen as subjects that have defied their life circumstances, and have constructed ideas of what the good life and happiness –a good, dignified, free, and happy life (as Krotz (2002 y 2004) puts it)– would be like. This utopian horizon which the subjects aspire to reach –its components, challenges, and strategies to make it closer– is something we try to make visible through the analysis of the three principal sub-categories that conform the three subsystems of the major system that our research delimits as its object.